Pembelajaran Bahasa Arab di Era Digital: Problematika dan Solusi dalam Pengembangan Media - Samsul Haq (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Stakeholders in the education world are striving to use technology as a tool to advance education, especially in the learning of Arabic language. By combining various media such as audio, visual, and text, learning can be improved and deepened compared to using only one type of media. Arabic is the second foreign language taught in Indonesia, so it is important to utilize technology in learning this language. Therefore, this research aims to describe the problems and solutions of Arabic language learning in the development of learning media. This research uses a qualitative design method and data is obtained from articles and reading sources related to the discussion topic. It can be concluded that linguistic problems include phonetics, morphology, and structure, while non-linguistic problems include learning motivation, learning facilities, teaching methods, learning time, and learning environment. Meanwhile, language learning problems also vary depending on the age of the students and different learning environments. Solutions in media development must be adjusted to linguistic and non-linguistic problems.